Well-Being on Lecturer: Reviewed from Gratitude and Religiosity - Nurwahidin, Muhammad (International Journal of Engineering and Technology, 2018)
Lecturers are a noble and more promising job. Many young people want to become lecturers. Nevertheless, more and more demands in developing a lecturers career will have an impact on well-being of lecturers. The purpose of this research is to know the role of gratitude and religiosity towards well-being of lecturers. The sample for this research is 123 lecturers from several universities in Jakarta. Data collection tools used in this study is the psychological scale of the scale of gratitude, the scale of religiosity and scale well-being. Result in this research is there is relationship of gratitude and religiosity to well-being.Â Â